PENGOLAHAN DATA CITRA SATELIT MTSAT MENGGUNAKAN APLIKASI SATAID (SATTELITE ANIMATIONS AND INTERACTIVE DIAGNOSIS) - Fadholi, Akhmad (Jurnal Informatika dan Komputasi STMIK Indonesia Jakarta, 2013)
Multi-functional Transport Satellites (MTSAT) is a weather satellite that was launched by the Japan Meteorology Agency (JMA) which produce satellite imagery. JMA develops an application to process the MTSAT satellite data, it is called Satellite Animation and Interactive Diagnosis or SATAID. It’s used to display satellite imagery and find some weather parameters value in satellite imagery by using Numerical weather Prediction (NWP) data. Processing MTSAT satellite data consist of two technics, they are displaying satellite data as cloud identification or nephanalysis and utilization NWP to analys weather parameters. These are the most frequently methods used in processing MTSAT satellite data.